Guqin Transmission in the Digital Age: A Posthumanist Perspective on Music Education - An, Na; Chuangprakhon, Sayam; Seekhunlio, Weerayut; Liu, Qianqian (Journal of Posthumanism, 2025)
The transmission of Guqin music, an ancient Chinese cultural tradition, is undergoing profound changes due to digital technology and artificial intelligence. This study examines the intersection of traditional Guqin pedagogy and digital innovation through a posthumanist framework, analyzing how digital tools influence preservation, accessibility, and authenticity. The research in Anhui Province employs ethnographic methods, including interviews with Guqin masters, students, and digital platform developers, to explore the integration of algorithmic learning, virtual performances, and online education. The findings reveal opportunities and challenges: while digital platforms enhance accessibility and engagement, they also disrupt embodied learning practices central to Guqin mastery. This study advocates for a hybrid educational model that merges traditional mentorship with digital augmentation, ensuring cultural sustainability without eroding the Guqin’s philosophical and artistic essence. Future research should further investigate the long-term implications of digital mediation in Guqin education and explore its broader cultural significance.